2014
DOI: 10.4212/cjhp.v67i4.1372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Once-Daily Vancomycin Regimen in an Outpatient Leukemia/Bone Marrow Transplant Clinic (OD-VANCO Study)

Abstract: Background:The Leukemia/Bone Marrow Transplant Program of British Columbia manages patients with high-risk febrile neutropenia and those with non-neutropenic immunocompromised states in an outpatient clinic setting. Because the program treats outpatients only, once-daily administration of IV antibiotics is desirable. A high-dose, once-daily vancomycin nomogram was developed and implemented as part of the antibiotic treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Recently, Suzuki and co‐workers had proposed a target Ctrough of 11.5 mg/mL for febrile neutropenia in patients with hematological malignancies . The high‐dose, once‐daily vancomycin nomogram attained trough levels greater than 10 mg/L in only 21% of patients with leukemia and a substantial number of adverse drug reactions were observed leading to the nonrecommendation of such regimen for outpatient therapy …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Suzuki and co‐workers had proposed a target Ctrough of 11.5 mg/mL for febrile neutropenia in patients with hematological malignancies . The high‐dose, once‐daily vancomycin nomogram attained trough levels greater than 10 mg/L in only 21% of patients with leukemia and a substantial number of adverse drug reactions were observed leading to the nonrecommendation of such regimen for outpatient therapy …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…86 The high-dose, once-daily vancomycin nomogram attained trough levels greater than 10 mg/L in only 21% of patients with leukemia and a substantial number of adverse drug reactions were observed leading to the nonrecommendation of such regimen for outpatient therapy. 87 The "PPK Model review" found three studies in hematological patients. One was excluded because it was not a population model and the remaining two are described in Table 12.…”
Section: Hematologic Patientsmentioning
confidence: 99%
“…Therefore, twenty-one sets of clinical data were finally included. In 18 studies, 17,18,20,[22][23][24][25][26][27][28][29][30][31][34][35][36][37][38] vancomycin was infused intermittently, and 2 studies adopted continuous infusion, 19,21 whereas the remaining 1 conference abstract did not report the specific dosing regimen. 16 For single-arm studies, nine studies included neutropenic hematologic patients consecutively, 16,18,20,21,26,28,31,34,35 while 6 studies included patients with hematologic malignancies without distinguishing neutropenia from non-neutropenia.…”
Section: Resultsmentioning
confidence: 99%
“…16 For single-arm studies, nine studies included neutropenic hematologic patients consecutively, 16,18,20,21,26,28,31,34,35 while 6 studies included patients with hematologic malignancies without distinguishing neutropenia from non-neutropenia. 17,19,22,27,29,38 Additionally, another two studies included hospitalized patients and took neutropenia as a risk factor. 30,36 Concerning comparative cohort studies, there were two studies comparing neutropenic patients with nonneutropenic patients, 23,25 and another 2 studies focused on the difference between hematologic malignant patients and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation